Is Two-Tier Health Care the Future? - Thomas, Bryan, 1973-; Flood, Colleen M. (Law, technology, and media., 2020)
Canadians are deeply worried about wait times for health care. Entrepreneurial doctors and private clinics are bringing Charter challenges to existing laws restrictive of a two-tier system. They argue that Canada is an outlier among developed countries in limiting options to jump the queue. This book explores whether a two-tier model is a solution. In Is Two-Tier Health Care the Future?, leading researchers explore the public and private mix in Canada, Australia, Germany, France, and Ireland. They explain the history and complexity of interactions between public and private funding of health care and the many regulations and policies found in different countries used to both inhibit and sometimes to encourage two-tier care, such as tax breaks. This edited collection provides critical evidence on the different approaches to regulating two-tier care across different countries and what could work in Canada.